Dyplomacja Stanów Zjednoczonych wobec Światowej Konferencji Rozbrojeniowej w latach 1932—1933 - Waszczykowski, Witold (Acta Universitatis Lodziensis. Folia Historica, 1983)
Debates of the Disarmament Conference took place partly during administration of H. Hoover and F. D. Roosevelt. Strategy of the American diplomacy towards disarmament problems discussed at the conference was elaborated by Hoover's administration. Through reduction of armaments, Hoover strove to solve a part of American economic problems both internal and external. Treaties on restriction of armaments were also to allow the United States to preserve the status quo in the Far East favourable for this country. Such were the aims of the armaments reduction plans, called Hoover's plan announced on June 22, 1932.